2012
DOI: 10.1089/tmj.2011.0215
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an e-Learning Curriculum on Occupational Health for Music Performers

Abstract: The findings suggest that the HPMP e-learning course enhanced student awareness of Practice and Performance issues but did not have as significant an impact on student awareness of Health and Lifestyle issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They recommend techniques such as visualization, breathing, relaxation, cognitive restructuring, and self-talk for performance anxiety (Barton and Feinberg, 2008 ; Clark and Williamon, 2011 ; Osborne et al, 2014 ; Spahn et al, 2016 ). They use behavioral exposure in the form of public performance (Clark and Williamon, 2011 ; Spahn et al, 2016 ) and offer classes in Feldenkrais Method and Alexander Technique (Zander et al, 2010 ; Su et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…They recommend techniques such as visualization, breathing, relaxation, cognitive restructuring, and self-talk for performance anxiety (Barton and Feinberg, 2008 ; Clark and Williamon, 2011 ; Osborne et al, 2014 ; Spahn et al, 2016 ). They use behavioral exposure in the form of public performance (Clark and Williamon, 2011 ; Spahn et al, 2016 ) and offer classes in Feldenkrais Method and Alexander Technique (Zander et al, 2010 ; Su et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, few health courses for conservatoire students have been designed with sufficient care, in our view; they have not been documented adequately, nor have they been evaluated thoroughly (e.g. Arnasson et al, 2018;Baadjou et al, 2018;Barton and Feinberg, 2008;Clark and Williamon, 2011;Laursen and Chesky, 2014;Lopez and Martinez, 2013;Su et al, 2012;Zander et al, 2010). None were based on comprehensive literature reviews and the only report of a course based in the UK (Clark and Williamon, 2011) focused on the evaluation of a mental skills programme rather than health education more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that tertiary music students want to learn more about musicians' MSSs, 71,72 with most wanting this education delivered in practical formats, including instrumentspecific workshops, and few interested in online delivery. 71 Previous research on musicians has also suggested that online health education programs have been ineffective in changing behaviour, 40 and have poor compliance. 73 Face-to-face programs developed with input directly from musicians themselves may be more successful.…”
Section: Education Programmentioning
confidence: 99%